Estudo dos processos aproximados utilizados para a consideração das não-linearidades física e geométrica na análise global das estruturas de concreto armado - Danielle Meireles de Oliveira (2007)
In this work, the simplified methods generally used to take into account physical and geometric non-linearities in reinforced concrete structures global analysis are studied. With this purpose, several plane frames and buildings of medium height are analysed using ANSYS software. The results provided which inertia reduction values, among thoserecommended by Brazilian Code, NBR 6118:2003, and BRANSON (1966) formulation, better represent the actual behavior of the structures. At the service limit state, the analysis that reduces the stiffness of columns in 20% and uses BRANSON (1966) equivalent inertia for beams was considered the most efficient. For the unfactored loading and at the ultimate limit state, the use of inertia reduction values recommended byNBR 6118:2003 for the most general cases showed to be the most appropriated. The accuracy of gz coefficient as magnifier of first order efforts (bending moments, axial and shearing forces) and as magnifier of horizontal loads to evaluate final second order efforts is also studied. It was checked that the gz coefficient should be used as magnifier of firstorder moments (and not for horizontal loads) to evaluate final second order moments. In case of axial force in columns and shearing force in beams, the magnification by gz coefficient is not necessary, since that, for these efforts, the values obtained in first and in second order analysis are almost the same. Finally, the simplified method to evaluate finalsecond order moments using the gz coefficient as magnifier of first order moments is studied considering the variation of the second order effects with the height of the buildings.